Budidaya Pakcoy (Brassica rapa L.) Terapung di Rawa Lebak dengan Volume Media Tanam Berbeda - Gustiar, Fitra; Agustina, Hilda; Purnama Ria, Rofiqoh; Tarinda, Gaby (Jurnal Hortikultura Indonesia, 2025)
The increasing population also increases the need for vegetables, so it is necessary to increase vegetable production. Floating system cultivation can be used as an alternative form to increase vegetable production by utilizing flooded land. One factor that can affect plant growth is the volume of planting media. This research was conducted to determine proper the volume of planting media in Brassica rapa L. cultivation using floating system as an effort to produce optimum production in swamp area cultivation. This research was carried out in the swamp research field laboratory Agronomy Department Sriwijaya University from July to September 2024. The research method used was a Randomized Complete Block Design (RCBD) with four treatments consisting of 1.9 liter (V1), 2.7 liter (V2), 3.6 liter (V3), and 5 liter (V4) planting media volume. This floating agriculture system used a raft made of bamboo and mineral water gallons measuring 1.3 m × 2 m with the approach hydroponic wick system and modified floating rafts. The research results showed that cultivating Brassica rapa L. with volumes of media using floating system produced the highest quality of growth per plant in 5 L media volume treatment (V4). Meanwhile, 1.9 L media volume treatment (V1) was able to accommodate larger a plant population with the highest production yield per raft unit.Keywords : floating rafts, flooded land, vegetables, wick system